Manajemen Mutu Terpadu dalam Meningkatkan Kinerja Sekolah SMK Ma’arif 1 Piyungan Bantul - Fauzi, Hafidh Nur (Universitas Pesantren Tinggi Darul 'Ulum, 2019)
Education is very important in improving the quality of human resource. The quality of education is a hope and a dream for community. Total Quality Management can improve school performance if it is applied appropriately. This research aimed to find out the programming, implementation programs, and factors affecting the implementation of Total Quality Management. This research employed descriptive method with qualitative approach. Technique of data collection used was interview, observation, and documentation. The research subjects were principal, teachers, and staffs. The results showed that the State Vocational High School Ma’arif 1 Piyungan Bantul refer to the principles of Total Quality Management in programming. The implementation of Total Quality Management involved all school elements. The beneficial implementation of Total Quality Management was to increase teachers’ performance in order to affect students’ achievement and school performance. The factors affecting were motivating factor and inhibiting factor. Motivating factors include a good quality of teachers and principal, an adequate infrastructure, a high level of trust and public interest of parents and school committee. The inhibiting factors include inadequate human resources and the incompatibility of teachers and staff’s performance with Total Quality Management.